2003
DOI: 10.1046/j.1444-2906.2003.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the distribution of bacteria, heterotrophic nanoflagellates and ciliates in Hiroshima Bay in summer

Abstract: The distribution of the main microbial loop components (bacteria, heterotrophic nanoflagellates (HNF), ciliates) was investigated at three sites: the inner, central and outer regions of Hiroshima Bay, Seto Inland Sea, Japan, in summer (June and August 1996 and July 1997). At the inner region site, lower salinity and higher concentrations of nutrients and chlorophyll a were observed than in the other regions. Bacterial, HNF and ciliate biomasses ranging from 32.6 to 170.1 µg C/L, from 1.5 to 84.8 µg C/L and fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…), we speculate that these results represent the response of these microorganisms to farm vicinity. The changes in bacterial abundances near fish cages are rarely reported and usually are registered outside the Mediterranean in eutrophic environments with more intensive aquaculture activities (Kamiyama, Arima & Tsujino ; Sakami, Abo, Takayanagi & Todo ). Rare studies in the Mediterranean seldom observed increase in bacterial abundances near cages (La Rosa et al .…”
Section: Discussionmentioning
confidence: 99%
“…), we speculate that these results represent the response of these microorganisms to farm vicinity. The changes in bacterial abundances near fish cages are rarely reported and usually are registered outside the Mediterranean in eutrophic environments with more intensive aquaculture activities (Kamiyama, Arima & Tsujino ; Sakami, Abo, Takayanagi & Todo ). Rare studies in the Mediterranean seldom observed increase in bacterial abundances near cages (La Rosa et al .…”
Section: Discussionmentioning
confidence: 99%
“…cultures examined in this study ranged 7.72 ¥ 10 5 -2.39 ¥ 10 6 cells/mL (Tables 2 and 3); these values were generally in the same range of bacterial counts in coastal sea waters (from 2.78 ¥ 10 5 to 5.75 ¥ 10 6 cells/mL). 15,17,18 The proportion of DVC positive cells to total bacteria in the Nannochloropsis sp. cultures averaged 46.0%.…”
Section: High Growth Potentialmentioning
confidence: 99%
“…Although PO 4 –P concentration was higher in Hiroshima Bay than Oginohama Bay, the concentrations of other nutrients were not significantly different between the two bays based on the monthly paired Student's t ‐tests. Chlorophyll‐ a concentration in Hiroshima Bay was higher than that in Oginohama Bay, implying that phytoplankton rapidly consume the riverine nutrients in the vicinity of the river mouth areas in Hiroshima Bay 11,18 . Lower concentration of PO 4 –P may also cause the higher annual mean value of the DIN : PO 4 –P ratio in Oginohama Bay.…”
Section: Discussionmentioning
confidence: 98%
“…Chlorophyll-a concentration in Hiroshima Bay was higher than that in Oginohama Bay, implying that phytoplankton rapidly consume the riverine nutrients in the vicinity of the river mouth areas in Hiroshima Bay. 11,18 Lower concentration of PO 4 -P may also Oginohama Bay (November to April). Data was standardized by the value for November in each bay.…”
Section: Environmental Conditions In Both Baysmentioning
confidence: 99%